Pengaruh User Generated Content dan Fear of Missing Out Terhadap Purchase Intention pada Produk Blind Box Pop Mart (Studi pada Generasi Z di Kota Malang) - Elvaretta Putri Vironicha; Lina Budiarti; Yosi Afandi (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
The rapid advancement of digital technology and the growing use of social media, particularly TikTok, create new phenomena in consumer behavior. One of the most notable phenomena is the rising trend of Pop Mart blind box products, driven by user-generated content (UGC) and fear of missing out (FOMO). However, not all exposure to these two factors automatically translates into purchase intention. Some consumers engage with such content merely for entertainment purposes, while the emotional impulse triggered by the scarcity of Pop Mart products may be temporary in nature. This study aims to analyze the partial and simultaneous effects of UGC and FOMO on purchase intention toward Pop Mart blind box products among Generation Z in Malang City.This study employed a quantitative approach with data collected through questionnaires distributed to 100 Generation Z consumers in Malang City, aged 16–30 years, who had been exposed to Pop Mart blind box content on TikTok. The respondents were selected using a purposive sampling technique. Data were analyzed using validity and reliability testing, classical assumption testing, multiple linear regression analysis, coefficient of determination analysis, and hypothesis testing with t- and F-tests, with assistance from SPSS. The findings revealed that user-generated content (UGC) had a positive and significant partial effect on purchase intention toward Pop Mart blind box products among Generation Z in Malang City, as indicated by a t-value of 5.841 and a significance value of 0.000 (< 0.05). Similarly, fear of missing out (FOMO) also had a positive and significant partial effect on purchase intention, with a t-value of 7.380 and a significance value of 0.000 (< 0.05). Furthermore, the simultaneous test showed that UGC and FOMO jointly had a positive and significant effect on purchase intention, as evidenced by an F-value of 62.918, which exceeded the F-table value of 3.09, with a significance value of 0.000 (< 0.05). The coefficient of determination (R²) indicated that UGC and FOMO explained 55.6% of the variance in purchase intention, while the remaining 44.4% was influenced by other factors not examined in this study. Based on the findings, it can be concluded that UGC and FOMO significantly influence purchase intention toward Pop Mart blind box products among Generation Z in Malang City. The combination of these factors has proven effective in shaping consumers' purchase intention. These findings highlight the importance of authentic social media content and psychological factors in influencing consumer behavior in the digital era.